Strategi Pembelajaran Oleh Guru dalam Meningkatkan Efektifitas Belajar Siswa Kelas X pada Mata Pelajaran Geografi di SMAN 1 Ngunut Tulungagung - Nabella Zubaida ’Izzatur Rohmah; Dita Hendriani (Sosial Simbiosis : Jurnal Integrasi Ilmu Sosial dan Politik, 2025)
This study is motivated by the teacher's learning strategies having a significant impact on student motivation, understanding, and learning outcomes so that students are expected to be able to learn effectively. The formulation of the problem in this study is: (1) How are the learning strategies used by teachers to improve the learning effectiveness of class X students in geography subjects at SMAN 1 Ngunut Tulungagung? (2) What are the obstacles for teachers in improving the learning effectiveness of class X students in geography subjects at SMAN 1 Ngunut Tulungagung? (3) What is the impact on students in the application of teacher strategies in geography subjects for class X at SMAN 1 Ngunut Tulungagung? The objectives of this study are (1) to determine the learning strategies used by teachers in improving the learning effectiveness of class X students in geography subjects at SMAN 1 Ngunut Tulungagung. (2) to determine the obstacles for teachers in improving the learning effectiveness of class X students in geography subjects at SMAN 1 Ngunut Tulungagung. (3) to determine the impact on students in the application of teacher strategies in geography subjects for class X at SMAN 1 Ngunut Tulungagung. This study uses a qualitative-descriptive approach with data collection through interviews, observations, and documentation. Data analysis is carried out through the stages of data reduction, data presentation, and drawing conclusions. Informants in this study include Geography teachers and class X students at SMAN 1 Ngunut Tulungagung and all parties involved. The results of the study indicate that the Learning Strategies used by teachers in improving the effectiveness of student learning in Geography Subjects at SMAN 1 Ngunut Tulungagung are 2, namely Expository and Inquiry Strategies. The obstacles experienced include: 1) lack of response in the learning process, 2) bad influence from friends, 3) sleeping in class. Impact on students in implementing teacher strategies in Geography subjects for class X The ability to draw conclusions, students are able to present conclusions in a coherent and sequential manner. This study recommends that teachers are expected to be active in participating in training, coaching which is usually held at school or outside school regarding learning strategies. For students, it is hoped that students can focus more on the subject matter taught by the teacher.